Implementation of Project-Based Learning Model In History Learning for Class X Students at SMA Negeri 9 Lubuklinggau - Melati Suci*; Yeni Asmara; Sarkowi Sarkowi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
This study aims to determine the completeness of history learning outcomes for students of class X SMA Negeri 9 Lubuklinggau for the academic year 2023/2024 after the implementation of the Project Based Learning Models. This type of research used quasi-experimental. The population is in all class X SMA Negeri 9 Lubuklinggau and as a sample, class X IPA 2 is taken randomly. The data was collected using a multiple choice test technique with 33 questions. Results Based on the research and discussion, it can be found that the results of learning history of students in class X SMA Negeri 9 Lubuklinggau after learning using the Project Based Learning method are significantly complete. This is in accordance with the results of the t-test, the post-test value at a significant level = 0.05, obtained t_count (11.17) t_table (1.708), the average student history learning outcome after the application of the Crossword Puzzle method was 82,32 and the proportion of students who have achieved complete learning reaches 75%.